PENGGANDAAN SKALA PRODUKSI BIOETANOL DARI TONGKOL JAGUNG - Arif, Abdullah bin; Diyono, Wahyu; Hayuningtyas, Maulida; Syaefullah, Enrico; Budiyanto, Agus; Richana, Nur (Informatika Pertanian, 2017)
The effort to search for alternative energy materials that do not compete with food and feed is necessary and urgent. Lignocellulosic biomass is one potential source of renewable energy. Scalinge up methodproduction of bioenergy production from laboratory scale to industrial scale needs to be studied and developed. The aim of this study is to find get scalinge up method o0f the bioethanol  production from corn cobs. An Eexperiments on scalinge up of bioethanol production from laboratory scale to industrial scale was is done by the Pg / V constant method (stirring power per volume). Scale up calculations based on data from fermented liquid rheological characteristics and specifications fermenters are used. The results showed that the calculation of basic scale up bioethanol production capacity bioreactor of 200 l, obtained working volume of 65% or 130 l, high of liquid fermentation  0.840 m, diameter tank bioreactor 0.441 m, diameter of a stirrer of turbine type of flat 0.187 m and the speed of agitation at 66.34 rpm. Based on  the calculation of basic scale up bioethanol production capacity bioreactor of 10,000 l, obtained working volume of 65% amounting to 6,500 l, high of liquid fermentation  2.87 m, diameter tank bioreactor 1.49 m, diameter of a stirrer of turbine type of flat 0.63 m and the speed of agitation at 29.52 rpm.